Effect of Li Termination on the Electronic and Hydrogen Storage Properties of Linear Carbon Chains: A TAO-DFT Study - Sonai Seenithurai (Nature Portfolio, 2017)
Abstract Accurate prediction of the electronic and hydrogen storage properties of linear carbon chains (C n ) and Li-terminated linear carbon chains (Li2C n ), with n carbon atoms (n = 5–10), has been very challenging for traditional electronic structure methods, due to the presence of strong static correlation effects. To meet the challenge, we study these properties using our newly developed thermally-assisted-occupation density functional theory (TAO-DFT), a very efficient electronic structure method for the study of large systems with strong static correlation effects. Owing to the alteration of the reactivity of C n and Li2C n with n, odd-even oscillations in their electronic properties are found. In contrast to C n , the binding energies of H2 molecules on Li2C n are in (or close to) the ideal binding energy range (about 20 to 40 kJ/mol per H2). In addition, the H2 gravimetric storage capacities of Li2C n are in the range of 10.7 to 17.9 wt%, satisfying the United States Department of Energy (USDOE) ultimate target of 7.5 wt%. On the basis of our results, Li2C n can be high-capacity hydrogen storage materials that can uptake and release hydrogen at temperatures well above the easily achieved temperature of liquid nitrogen.